1985
DOI: 10.1177/019262338501300405
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Pathologic Changes Induced by the Long-term Administration of Contraceptive Steroids to Rodents

Abstract: The induction of pathologic changes with hormone steroids has been studied in rodents, although comprehensive studies are lacking on the potential reversibility of these lesions. For these purposes, groups of rats were treated with quingestanol acetate and quinestrol, a progestogen-estrogen combination, for 50 weeks and observed for a subsequent 30-week period. Treatment resulted in a significant body weight gain suppression and reduction of food consumption which recovered after withdrawal. Other significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Interestingly, a recent randomized trial conducted in China found that subjects given a combination of niacin and riboflavin (which helps maintain levels of the antioxidant glutathione) were at increased risk of posterior subcapsular cataract (17). A small study in rats found that a combination of estrogen and progestin led to increased cataract formation (18). Further basic biologic research is needed on the effect of estrogen on the lens.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent randomized trial conducted in China found that subjects given a combination of niacin and riboflavin (which helps maintain levels of the antioxidant glutathione) were at increased risk of posterior subcapsular cataract (17). A small study in rats found that a combination of estrogen and progestin led to increased cataract formation (18). Further basic biologic research is needed on the effect of estrogen on the lens.…”
Section: Discussionmentioning
confidence: 99%
“…50 The pituitary changes were sufficient to displace the brain and raise intracranial pressure with resultant early death in some animals. The daily treatment schedule resulted in average pituitary weights of over 80 mg and the weekly treatment over 120 mg per 100 g body weight (compared with control mean of approximately 5 mg/100 g body weight).…”
Section: Diffuse Hyperplasiamentioning
confidence: 99%
“…Despite these variable histological and cytological features, the largest proportion of spontaneous rat pituitary adenomas contains prolactin. 50 Massively enlarged pituitary glands, sufficient to cause severe signs of compression of the central nervous system regressed upon withdrawal of treatment raising the possibility that lesions diagnosed as pituitary adenomas may not all be autonomous neoplastic lesions. Some are totally unreactive to antisera to all the usual pituitary hormones.…”
Section: Ratsmentioning
confidence: 99%
“…Rats treated with oral contraceptives containing estrogen and progestogen have an increased incidence of cataracts compared with nontreated controls, suggesting that estrogens may actually promote cataract formation (15). However, the effectiveness of estrogen in these treatments is not certain, because the uteri of the treated animals were atrophic (15); progestogen may have produced a predominantly antagonist effect. In another study, long-term treatment with the antiestrogen tamoxifen increased the incidence of cataracts in rats (16).…”
mentioning
confidence: 99%